Tax Literacy for Students Using TikTok Media: An Experimental Research - Prawira, Ida Farida Adi; Apandi, R. Nelly Nur; Abdurrauf, Umar (Universitas Syiah Kuala, 2023)
Objective This paper investigates the differences in the understanding of students regarding taxation before and after the tax literacy process was carried out using TikTok media.Design/methodology This research was conducted using the experimental method. The respondents to this experiment were 88 grade 6 elementary school students. 66 junior high school students and 37 high school students. The research design used the Pretest-Posttest Control Group Design.Results Learning about taxes needs to be applied as early as possible to raise public awareness about the benefits of taxes in the state's life, as the saying, catch them young. The authors concluded that after utilizing TikTok instructional materials, pupils' comprehension of taxation differed. Students will find it easier to comprehend the established learning objectives when learning entails offering them experiences. TikTok learning content regarding taxes made has brought students to understand tax practices in the real world. Through pictorial and sound impressions, not just reading paper which is static.Research limitations/implications This study did not specifically outline the student's task in critical analysis of events that should have been an important part of the learning process. In addition, it did not compare with the conventional learning group hence it is unknown whether TikTok is more acceptable.Novelty/Originality This research contributes to teachers in schools to develop instructional media with a short and interactive duration of time, so that it will make students understand the material easier and more enjoyable. Instructional media using social media has been carried out a lot, but in this study the use of TikTok media is a new media used in tax literacy and this media is still very happening.